2022
DOI: 10.1111/ases.13030
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting aneurysm of the proper hepatic artery after laparoscopic hepatectomy possibly related to the Pringle maneuver: A case report

Abstract: In hepatectomy, the Pringle maneuver is commonly used, but its association with iatrogenic injury is not yet well understood. This report presents a case of dissecting aneurysm of the proper hepatic artery (PHA) possibly associated with the Pringle maneuver during laparoscopic hepatectomy, that was successfully treated by transcatheter arterial embolization (TAE). The patient was a woman in her 70s, and repeat hepatectomy for liver metastasis of rectal neuroendocrine neoplasm was planned. She underwent hand-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The advantage of this approach is that the in vitro operation is relatively convenient compared with the in vivo operation, which saves operation time. The drawback is that one of the potential disadvantages of using additional cannulas for extracorporeal PM (as compared with intracorporeal PM) is the risk of gas leakage from the abdominal cavity [19], and the secondary narrow strip may sometimes cause injury to the conduit within the hepatoduodenal ligament [20,21]. Onda S et al [22] reported a new laparoscopic Satinsky vascular clamp.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of this approach is that the in vitro operation is relatively convenient compared with the in vivo operation, which saves operation time. The drawback is that one of the potential disadvantages of using additional cannulas for extracorporeal PM (as compared with intracorporeal PM) is the risk of gas leakage from the abdominal cavity [19], and the secondary narrow strip may sometimes cause injury to the conduit within the hepatoduodenal ligament [20,21]. Onda S et al [22] reported a new laparoscopic Satinsky vascular clamp.…”
Section: Discussionmentioning
confidence: 99%
“…If the external tube is not tightly clamped, it could easily cause pneumoperitoneum leakage. Moreover, reports suggest that narrow cloth strips may sometimes cause damage to the blood vessels within the hepatoduodenal ligament, leading to hepatic artery aneurysm and portal vein thrombosis [ 17 , 18 ]. Another disadvantage of extracorporeal occlusion is that it can be challenging to perform when the patient is in the left lateral decubitus position [ 19 ].…”
Section: Discussionmentioning
confidence: 99%